Candidate gene analysis of quantitative trait variation in flowering time in almond (Prunus dulcis (Mill) D.A. Webb) - Silva C.; Sánchez A.M.; García-Mas J.; Arús P.; Oliveira M.M. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
The identification of genes involved in flower development and blooming time could be important to assist breeders in creating new late flowering cultivars as well as to understand the complex process of flower induction in a fruit species like almond. A major gene and some quantitative trait loci (QTLs) for blooming time were previously detected and localized on the Prunus genome. The aim of this work was to associate these QTLs to known genes using a candidate gene approach. Two cDNAs putatively encoding protein homologs to Arabidopsis flower genes were isolated from almond flower buds. A Prunus EST database was screened and ten ESTs were selected by their matches with genes known to be involved in flower development in other plant species. Molecular markers were developed from these candidate genes for mapping on the almond 'Texas' x peach 'Earlygold' F2 population. Twelve candidate genes were assigned to seven linkage groups in the Prunus genome.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)